The Digital Monster transmedia as a credence-mythological patchwork: syncretism and reconfigurations of myths, legends, and beliefs in the configuration of the Digimon World - Ojeda-García, Francisco Miguel; Ogáyar-Marín, Francisco Javier (Amaltea. Revista de Mitocrítica, 2022)
Digimon arrived in Spain in 1999, quickly becoming a popular series for children and teenagers. Set in a digital environment inhabited by digital monsters: the Digital World; exploits tropes associated with traditional mythical and belief systems and exports them to the present day, through a syncretic exercise and establishing a link with the digital context. Thus, feeding on contemporary “technomyths”, new hybrid mythical realities emerge, which are faithful reflections of the human attitude towards digitally mediated experiences. Through the content analysis of the 253 chapters that make up the first seasons of the series, the article aims to understand the ways in which mythic narratives are transformed and hybridised in today's mass media, using the transmedia Digital Monster as a context for these processes.